Longstanding Retained Foreign Body in Orofacial Region: A Diagnostic Challenge - Dharel, Santosh; Koirala, Bandana; Dali, Mamta; Birajee, Gajendra (Journal of Nepalese Association of Pediatric Dentistry, 2023)
Trauma induced orofacial injuries have chances of embedment of foreign bodies into facial tissues which may lead to the development of distressing signs and symptoms. Advancement of the diagnostic modalities have made foreign body detection easier; however, they still have limitations. So, a careful clinical examination along with proper history is mandatory before choosing any diagnostic modalities. A 19-month-old boy suffered a month-long pus discharge from his cheek after a fall 6 months back. Despite X-rays and ultrasounds, the cause remained unclear. Based on the clinical history along with clinical assessment, retained foreign body was suspected. Surgical exploration of the site under local anesthesia resulted in to the removal of two wooden pieces of sizes approximately 3×0.6x×0.3 cm3 followed by oral antibiotics led to the uneventful healing of the wound. Detailed case history, proper examination with the aid of diagnostic modalities led to the successful removal of foreign body.